AMİNOOKSİM LİGANDLARI İLE KOMPLEKSLERİNİN SENTEZİ VE KARAKTERİZASYONU - DUMAN, SİBEL (Fırat Üniveristesi, 2008)
Bu çalışmada, üç basamakta elde edilen 1,2-bis(o-aminofenoksit)etan'ın mutlak etanoldeki çözeltisi ile iki basamakta elde edilen anti-kloroglioksim'in mutlak alkoldeki çözeltisi 12 saat karıştırıldı. Bu karışım sonunda N,N?-[4,4?-{etan-1,2-diilbis(oksi)bis(4,1-fenilen)}bis(N?-hidroksi)-2-(hidroksiimino)asetimidamid] (L1H4) elde edildi. Diğer ligandlar N,N?-[3,3?-{etan-1,2-diilbis(oksi)bis(3,1-fenilen)}bis(N?-hidroksi)-2-(hidroksiimino)asetimidamid] (L2H4) ve N,N?-[2,2?-{etan-1,2-diilbis(oksi)bis(2,1-fenilen)}bis(N?-hidroksi)-2-(hidroksiimino)asetimidamid] (L3H4) aynı metodla elde edildi. Bu ligandlar (L1H4, L2H4, L3H4) ile Cu(OAc)2.H2O, Ni(OAc)2.4H2O, Co(OAc)2.4H2O, Zn(OAc)2 ve Cd(OAc)2 metal tuzlarının reaksiyonu sonucu kompleksler sentezlenmiştir.Önerilen yapılar L1H4'ün Cu(II) ve Co(II) kompleksleri için oktahedral, Ni(II), Zn(II) ve Cd(II) kompleksleri için tetrahedraldir. L2H4'ün Cu(II) ve Ni(II) kompleksleri için kare düzlem, Co(III), Zn(II) ve Cd(II) kompleksleri için oktahedral yapı önerilmiştir. L3H4'ün Cu(II) kompleksi tetrahedral, Ni(II) kompleksi kare düzlem iken Co(II), Zn(II) ve Cd(II) kompleksleri için oktahedral yapı önerilmiştir.Bu ligand ve onların komplekslerinin yapıları elementel analiz, UV-Vis, IR, 1H-NMR spektroskopisi, magnetik susseptibilite, erime noktası tayini, TGA ve DTA teknikleri ile karakterize edildi.

In this study, the solution of 1,2-bis(o-aminophenoxy)ethane in absolute ethanol, which was obtained by the three stages, was added to a stirred solution of the anti-chloroglyoxime in absolute ethanol, which was obtained two stages. After the addition was completed, the stirring was continued for 12 h. Then, N,N?-[4,4?-{ethane-1,2-diylbis(oxy)bis(4,1-phenylene)}bis(N?-hydroxy)-2-(hydroxyimino)acetimidamide] (L1H4) has been obtained. The other ligands N,N?-[3,3?-{ethane-1,2-diylbis(oxy)bis(3,1-phenylene)}bis(N?-hydroxy-)2-(hydroxyimino)-acetimidamide] (L2H4) and N,N?-[2,2?-{ethane-1,2-diylbis(oxy)bis(2,1-phenylene)}bis(N?-hydroxy)-2-(hydroxyimino)acetimidamide] (L3H4) were obtained using the same method. The complexes were synthesized by the reaction of these ligands (L1H4, L2H4, L3H4) with Cu(OAc)2.H2O, Ni(OAc)2.4H2O, Co(OAc)2.4H2O, Zn(OAc)2 and Cd(OAc)2 metal salts.The suggested structures for the L1H4 complexes of Cu(II) and Co(II) are octahedral, and for the Ni(II), Zn(II) and Cd(II) complexes are tetrahedral. Square-planar structures are suggested for the L2H4 complexes of Cu(II)and Ni(II); its complexes of Co(III), Zn(II) and Cd(II) are octahedral. Octahedral structures are suggested for the L3H4 complexes of Co(II), Zn(II) and Cd(II), whereas the Cu(II) complex is tetrahedral and the Ni(II) complex is square-planar.The ligands and their complexes have been characterized by elemental analyses, UV-Vis, IR and 1H-NMR spectra, magnetic measurements, and performing of melting point, TGA and DTA techniques.
The synthesis and characterization of aminooxime ligands with its complexes
Keywords: Kimya